Zimbabwean plantation workers conditions of work and service, a case of manicaland province. - Makaye, Peter; Munhande, Constantine (Midlands State University, 2014)
The colonial state the world over has been characterized as brutal and exploitative in that it denied the indigenous peoples from benefiting from their resources. In the case of Zimbabwe in particular, the settlers during the greater part of the first half of the 20th century took recourse to primitive accumulation of wealth as the hoped for Eldorado's failed to materialize. Following the failure of the "Second Rand" by the turn of the century, the settlers turned to agriculture. This resulted in a well calculated and managed process of land expropriation from the indigenous Africans. Thus agriculture became the backbone and corner stone of the colonial economy. African conditions of work and service in this sector have been regarded as the worst compared to other sectors and this history is well documented. The nationalist movements in their struggle against the colonial state pledged to improve the conditions of farm and plantation workers should they gain power. Was this promise fulfilled? This is the major question this paper grapples with. Basing on evidence gathered from plantations in Manicaland, it is argued in here that conditions of plantation as well as other farm workers have remained pathetic.